(untitled) (Research, Society and Development, 2022)
Amazonian biodiversity is considered the largest on the entire planet in terms of expansion and number of species. Therefore, this study aimed to inventory the diversity of butterflies present in a forest fragment located in the municipality of Abaetetuba, Pará. field for six months; (b) Identification of collected material and calculation of diversity indices and (c) Storage of specimens in the zoological collection of the Biodiversity and Conservation Laboratory (LABICON) of the Federal Institute of Pará (IFPA). As a result, 184 individuals belonging to 5 families were collected, distributed in 11 subfamilies and 20 species, with Nymphalidae as the family with the greatest richness (75%) and also the greatest abundance (74%). At the subfamily level, the most representative was the Heliconiinae subfamily (45%). Regarding species abundance, Anartia jatrophae and Hypothyris euclea showed greater abundance, with respectively (28; 25 individuals). The Shannon-Wiener diversity index (H’) found was H’ = 2.74, considered median for diversity, in addition, considering the data between rainfall periods, the comparison of indices by the “t” test showed no difference significant. The number of butterflies at LABICON increased from 212 to 396, with the inclusion of two more entomological boxes in the collection. It is concluded that further studies in the area are necessary in order to obtain a more comprehensive knowledge about the butterfly fauna in our region.